Factors Influencing Debt Financing within State-owned Corporations in Kenya - Nyamita, Micah Odhiambo; ., Nirmala Dorasamy (Journal of Economics and Behavioral Studies, 2014)
Debt financing is deemed crucial for economic development, as evidenced by the positive relationship between financial deepening and economic growth. Majority of studies on debt financing have been undertaken using data from developed economies, focusing more on private sector nonfinancial corporations. This study, therefore, attempts to fill the gap in the literature by investigating the factors influencing debt financing, using data from corporations within the public sector and from a developing economy. The study applied the fixed effects (FE), random effects (RE) and the general methods of moments (GMM), using the panel data regression analysis. Profitability, asset tangibility and corporation growth, were identified to be the main factors influencing debt financing within state-owned corporations in Kenya.